Pengembangan Aplikasi Absen Online Menggunakan Model Prototype di Sekolah Dasar Negeri Nagrak Tigaraksa - Desyani, Teti; Gymnastiar, Ahmad Raihan; Adam, Bani; Sunardi, Rizki Utama; Dwiardi, Stanislaus Dimas; Munawaroh, Munawaroh (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
The current attendance system requires a new system update. Because doing this would be very good for the institution of education, viewed from the sides as efficient, effective, quick, mastered and transparent. This would require a design before the system was built that would reveal the problems and solutions to the existing system. The online attendance system design is used to accelerate absenteeation by feedback that will then connect to android smartphone or ios through the whatsapp application owned by the student's parents. This requires an Internet link connected by smartphone on each parent. To create a report by the methods of the above system requires a workable data-collection system, with prototype methods and testing as establishment of an adequate proposal system as alternative to the best solution of the problem in the institution of education.